Du châtiment à la vengeance : Le prince et la vérité du crime à la fin du Moyen Âge - Marie-Hélène Méresse (Criminocorpus)
At the end of the Middle Ages, while the royal power gradually strengthens and centres around the figure of the prince, his political action remains ruled by the christian morality and the purpose of the common good. The abundant political and didactic literature, though, reflects the reality (and the apprehension?) of an evolution: at the dawn of the modern Sate, the arts of government and the power relations are changing. Are they the sign of a necessary adjustment, or the expression of an overwhelmed power? By the examination of some specific violent episodes of justice described by narrative sources of the 14th and 15th centuries, this article tends to observe the reactions of the prince when the latter chooses to answer by the use of the force, beyond customs and expectations. As extreme displays of the sovereign power (or, of a power seeking for sovereignty), these “cruelties” seemed to shock the contemporaries. Beyond the set-up speech and the prince's justification, the necessity of such acts, as well as the moral and political impact of punishment, is in question. How to understand the prince's decision when it fits no longer with the balanced use of force (and mercy) that a good government requires? When the punishment of the prince suddenly gets the appearance of a personal vengeance, the question of a legitimate violence must cope with many rhetorical and formal obstacles in order to find its place in the discourse of the sovereignty.